METODE EKSPERIMEN DALAM PENELITIAN PENDIDIKAN SEJARAH - Niara, Kautsar; Hotimah, Iis Husnul (Universitas Negeri Gorontalo, 2024)
This research explains the use of experimental methods in historical education research, highlighting its origins, theories, processes, and trends. Originally used in science and psychology, this method is now applied in history education. Its accuracy helps overcome the complexity of history learning issues. Data was collected from various sources, confirming the effectiveness of the experiments in this study. This method has been proven to be accurate, facilitating research in an increasingly complex field, and reflecting the evolution and adaptation of research methodology across disciplines.